Application Of Shotcrete At Oryx Mine - D. P. Venter (The Southern African Institute of Mining and Metallurgy, 1998)
When Oryx Mine down-scaled in 1994, focus was placed on development, with the primary aim being the exposure and proving of ore reserves. In order to achieve this aim, development ends had to be advanced to reef at the maximum possible rate. This in turn called for support methods which could keep up with the advancing faces, taking up minimum space and time for installation, while providing on the face a real coverage and effective long-term support. In the majority of the development ends which were located in fairly competent ground, the grouted rod development support proved to be adequate until such time as secondary support in the form of meshing and lacing could be installed. The ends developing towards the eastern boundary of the mine, especially in the ?C? block, encountered extremely adverse ground conditions due to the presence of smectite zones within the footwall quartzites. Smectites are a group of montmorillonite clay materials, mainly composed of hydrous aluminosilicates. They occur as minute platy crystals in the rock mass and are especially notable for their ability to absorb liquids. Generally, the zones are found in between the bedding planes of the host rock, and may vary considerably in thickness over short distances. Wherever the smectites were exposed by the development blasting, the rockwalls weathered as the smectites absorbed water and the condition of the tunnel rockwalls deteriorated rapidly. When the smectites were left exposed and allowed to weather, it became almost impossible to install secondary permanent support such as meshing and lacing at a later stage. To minimise the exposure time and subsequent deterioration of the smectite zones, it was recommended that all development ends encountering smectites be shotcreted as soon as possible after blasting. In developing a shotcreting support methodology, both a drycreting and wetcreting system were investigated. The situation at the time ruled out the use of a wetcreting system on the basis of the extensive and costly infrastructure required, as well as its limited manoeuverability. Instead, it was decided to opt for as maller scale but more manoeuverable drycreting system. The system utilized a number of portable drycrete machines with pre-bagged cement, which could support several development ends in close proximity. Initial trials using normal 30 MPa shotcrete on 19level proved successful and the system was implemented.